2021
DOI: 10.1002/hpm.3146
|View full text |Cite
|
Sign up to set email alerts
|

Health workforce response to Covid‐19: What pandemic preparedness planning and action at the federal and state levels in Germany?

Abstract: Introduction:The Covid-19 pandemic has required countries to prepare their health workforce for a rapid increase of patients. This research aims to analyse the planning and health workforce policies in Germany, a country with a largely decentralised workforce governance mechanism. Methods: Systematic search between 18 and 31 May 2020 at federal and 16 states on health workforce action and planning (websites of ministries of health, public health authorities), including pandemic preparedness plans and policies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…During the first wave of the pandemic health workforce capacity was scaled-up through a number of measures (39,47), yet HCW shortage still remained a major problem. Köppen et al concluded from their review, that health workforce planning was limited in the pandemic response plan and 'actions during the peak of the pandemic varied considerably across states' (54). HCW protection policy focused on physical protection, vaccination prioritisation of HCWs and bonus payment for frontline HCWs (12).…”
Section: The German Health System: Pandemic Protection Of Hospital Hc...mentioning
confidence: 99%
“…During the first wave of the pandemic health workforce capacity was scaled-up through a number of measures (39,47), yet HCW shortage still remained a major problem. Köppen et al concluded from their review, that health workforce planning was limited in the pandemic response plan and 'actions during the peak of the pandemic varied considerably across states' (54). HCW protection policy focused on physical protection, vaccination prioritisation of HCWs and bonus payment for frontline HCWs (12).…”
Section: The German Health System: Pandemic Protection Of Hospital Hc...mentioning
confidence: 99%
“…in intensive care or emergency care, or attracting medical and nursing students in their final year of studies to work. Some countries recruited retirees back into active practice, hired volunteers or professionals and students from other European countries [ 7 – 9 ]. These strategies have had implications on the skill-mix of the workforce, competencies and teamwork.…”
Section: Implications and Lessons Learned From The Covid-19 Pandemicmentioning
confidence: 99%
“…Therefore, compliance is of utmost significance for administrative controls to be effective and successful; even high-principled people sometimes make mistakes in terms of adherence to the rules. Prompt recruitment of trained healthcare professionals has also been suggested to enhance the performance of the existing healthcare system and scale-up public healthcare facilities [146,147].…”
Section: Administrative Control Measuresmentioning
confidence: 99%
“…Risk mitigation also depends on numerous safety measures that promote best practices for handling the SARS-CoV-2 crisis. Engineering controls refer to improving physical barriers among risk sources and health workers [146]; it is the most preferred measure to reduce transmission risk. Engineering control measures may provide solutions to ensure the physical separation of operations to treat infected persons through mechanical and physical means [63].…”
Section: Engineering Control Measuresmentioning
confidence: 99%